2018
DOI: 10.1002/acr.23332
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Magnetic Resonance Imaging for Grading of Subglottic Stenosis in Patients With Granulomatosis With Polyangiitis: Correlation With Pulmonary Function Tests and Laryngoscopy

Abstract: MRI and laryngoscopy provide comparable results for grading of SGS in GPA and correlate well with PFT. MRI is an attractive noninvasive and radiation-free alternative for monitoring the severity of SGS in patients with GPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Biopsy findings of the trachea or bronchi are usually nonspecific [ 32 , 33 ]. Thin-section CT helps in the assessment of the depth of tissue spread [ 34 - 36 ]. MRI and laryngoscopy provide comparable results for grading of subglottic stenosis in GPA and correlate well with pulmonary function testing [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy findings of the trachea or bronchi are usually nonspecific [ 32 , 33 ]. Thin-section CT helps in the assessment of the depth of tissue spread [ 34 - 36 ]. MRI and laryngoscopy provide comparable results for grading of subglottic stenosis in GPA and correlate well with pulmonary function testing [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Good correlations between spirometry outcomes and lumen areas suggest that MRI measurements could aid in understanding the anatomical substrate causing airflow obstruction, as indicated by a previous study. 14 A more affordable and widely available alternative method could be flexible nasal endoscopy, however, this method is unsuitable to evaluate anatomy below the vocal cords, is non- quantitative and can be challenging in case of arytenoid prolapse. Therefore, we consider flexible nasal endoscopy not a realistic alternative to laryngotracheoscopy nor to MRI.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important for laryngeal diseases with complex anatomy, such as laryngotracheal stenosis, laryngoceles, and haemangioma which are easily identified on MRI . Most selected studies compared the anatomy as shown on MRI to CT. No pediatric studies comparing MRI to laryngoscopy were found, but a comparative study in the adult population shows promising results in favor of MRI …”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric population, the choice of the right modality should be carefully considered according to the wide variety of pathologies and the patient's age. Direct laryngoscopy is the gold standard for early diagnostics of the pediatric larynx and vocal cords, but its disadvantages are the operator‐dependant diagnostic accuracy, the absence of objective measurements, limited detailed imaging, and the need for anesthetics to get a clear view of the subglottis . Computed Tomography (CT) is used for extensive imaging of the larynx after surgical intervention.…”
Section: Introductionmentioning
confidence: 99%